Church profiles basic information on member churches and associate members. (National Council of Churches in the Philippines, Research and Documentation Office, 1989)
A Church profile is a directory where you can find some basic data about the organization, the programs, history and declaration of faith, church workers and membership, and ecumenical linkages of our main ecclesial constituencies. It illustrates the manner of service and where ecumenical work takes place.